Work/ Life Balance Implementation Motives, Obstacles and Facilitators - Tramboo, Burhan (2008)
The growing competitive business environment has resulted in a situation where organizations are faced with number of strategic decisions in search of growth. The ever increasing pressure of globalization has created a boundary less economy which drives the organizations to adopt the appropriate strategy not only for the growth but also to create sustainable competitive advantage. The push for managing work/ life balance seems to have emerged out of ever increasing diversity as a result of changing demographics of the employment and as well as the changing societal values and globalization of markets (Way, 1999). Work/ life balance seems to be the most appropriate option open to them, and this is the concept being explored in this study. The objective of this study is to explore work/ life balance as a concept with a focus on how it is being used by the companies selected for this research. The study highlights the various motives for which the organizations feel the need for work/ life balance which include recruitment and retention of valuable work force, reduced absenteeism, reduced employee stress, health benefits, job satisfaction, and better life balance. It elaborates on the different types of work/life initiatives introduced by the companies such as child care program, part-time work, flexible work schedules, elder care, and working from home, leave arrangements. The study also touches upon the evolution of work/ life balance over the years and also the obstacles such as lack of resources, lack of co-worker support, and career consequences which impede the successful implementation of the work/ life balance. The discussion of the facilitators which assist in the effective implementation of the work/ life balance is also presented. Qualitative research method, specifically using the case study approach adopted for this study made possible the in depth analysis of the cases based on key issues, which are motives for work/ life balance in terms of the benefits to both employers and employees, obstacles in the implementation and facilitators which assist in the effective implementation of the policies. This study is explanatory in nature. Case study research involved work/ life balance strategies in organizations selected around the globe and was undertaken on sample size of twenty four cases. By exploring the different aspects of the work/ life balance in the companies selected from different parts of the world, we hope to gain significant insight on what is going on in these organizations with respect to work/ life balance with a view to possibly arrive at a conclusion that may lay a foundation for further survey-based research on work/ life balance.